Fizicheskie uprazhneniya v terapii dykhatel'noi nedostatochnosti u sportsmenov s zakrytoi cherepno-mozgovoi travmoi - Martynikhin, V. S. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this paper was to discuss the problem of physical exercises' using in the theraphy of the respiratory insufficiency in the athletes with a closed skull injury. It is shown that the early procedures of the medicinal gymnastics, when using the respiratory exercises of dynamic and static character, help to reach the pulmonary ventilation's improvement, create the better conditions for circulation in the pulmonary parenchyma as well as the peripheral bloodstream. The recommended rehabilitational measures allow not only to improve the function of the external respiration and to decrease the number of pulmonary after-effects, but they create the favourable prerequisits for the further rehabilitation of the patients with the closed skull injuries at the later stages of the treatment, also.